Concepts and comments : - Ackert, Patricia (Holt Rinehart & Winston, 1985)
Concepts and Comments, 2/e brings to the forefront a text for high-beginning to low-intermediate learners. This text supplies 25 additional thematic units which systematically recycle vocabulary while simultaneously teaching reading skills.